A new prognostic model including platelet/lymphocyte ratio and International Prognostic Score 3 for freedom from progression in patients with previously untreated advanced classical Hodgkin lymphoma. Issue 5 (3rd March 2022) - Tao, Yunxia; Chen, Haizhu; Zhou, Yu; He, Xiaohu; Qin, Yan; Liu, Peng; Zhou, Shengyu; Yang, Jianliang; Zhou, Liqiang; Zhang, Changgong; Yang, Sheng; Gui, Lin; et al.
Abstract: Purpose: We aimed to develop a new risk stratification tool to predict freedom from progression (FFP) for newly diagnosed advanced classical Hodgkin lymphoma (cHL). Methods: We collected data from 386 patients with advanced cHL diagnosed between December 8, 2000 and October 29, 2018, and treated with curative intent with ABVD (doxorubicin, bleomycin, vinblastine, and dacarbazine) or an ABVD‐equivalent regimen. Cases were randomly divided into training and validation cohorts at a ratio of 7:3. The new model was constructed based on the results of Cox proportional hazards model in the training cohort. Comparisons of discrimination between the new model and other models in the training and validation cohorts for FFP prediction were measured by time‐dependent area under curve (tAUC) and Harrell's C‐index. Calibration plots were constructed to compare the consistency between the predicted and observed estimates of survival probability for the new model in the training and validation cohorts. Results: The new model (IPSPLR) composed of International Prognostic Score (IPS)‐3 and platelet/lymphocyte ratio (PLR) provided four distinct risk groups. The IPSPLR showed better discriminative ability when compared with IPS‐3 and IPS‐7. The AUC of IPSPLR was consistently higher than that of IPS‐3 and IPS‐7 between 12 and 120 months. The C‐index of the IPSPLR was higher than that of IPS‐7 and IPS‐3. The calibration plots showed an excellent agreement between the IPSPLR‐predicted and observed estimates of 5‐year FFP. Conclusion: The IPSPLR is an easily used tool for FFP prediction for newly diagnosed advanced cHL. Validation of this tool in other large datasets is needed. Abstract : Graphical abstract: We developed a new model using the independent risk factors for freedom free progression in the multivariate Cox regression analysis. In the validation cohort, the new showed better in discriminating low‐ and high‐risk subgroups compared with International Prognostic Score (IPS)‐3 and IPS‐7. The time‐dependent area under curve for the new model was higher than that for IPS‐3 and IPS‐7 between 12 and 120 months in the validation cohort.